THE EFFECT OF PRODUCT QUALITY, SERVICE QUALITY, AND BRAND IMAGE ON CONSUMER PURCHASE DECISIONS AT AXL COFFEE - Budiyono; Suprihati; Agus Subekti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to examine the significant influence of product quality, service quality, and brand image on consumer purchasing decisions at Axl Coffee. The research was conducted at the café, with the population consisting of all consumers. A total of 100 respondents were selected as the sample using a purposive sampling technique, namely sample selection based on specific considerations. Data analysis was carried out using multiple linear regression, supported by t-tests, F-tests, and the coefficient of determination (R²). The t-test results show that product quality, service quality, and brand image each have a significant partial effect on purchasing decisions. Meanwhile, the F-test confirms that the three variables simultaneously have a significant influence on purchasing decisions.